Frosty the snowman [videorecording (DVD)] - Durante, Jimmy, 1893-1980; De Wolfe, Billy, 1907-1974; Vernon, Jackie; Laws, Maury; Nelson, Steve, 1907-1981 (Classic Media ; Distributed by Vivendi Entertainment, 2010)
Frosty the Snowman goes where he's needed most, and the town of Evergreen sure needed a visit. Mr. Tinkerton, the mayor, runs a tight ship, and there's no room for talk of magic or any other such nonsense. But, when Frosty the Snowman comes to town, he shows the town's children that magic is real.